Implementation of Risk Management BSI Griya Hasanah product at bank "X" - Bimo, Widhi Ariyo; Pahira, Siti; Azmia, Nora (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Financing is the main activity of Islamic banks in channeling funds to the community. One of the financing products is Home Ownership Loans (KPR). Risk management is a series of procedures and methodologies that can be used to identify, measure, monitor and control risks arising from the bank's business activities. The research method used is a qualitative method with the formulation of descriptive problems to obtain data by means of interviews and literature studies. Results The application of risk management in home ownership financing or Griya Hasanah is in accordance with Bank Indonesia regulations Article 3 of Bank Indonesia Regulation No: 13/23 / PBI / 2011 that the implementation of risk management includes at least (a) active supervision of the board of commissioners, directors, and sharia supervisory board (b) adequacy of policies, procedures, and determination of risk management limits and (c) adequacy of the process of identifying, measuring, monitoring, and controlling risks and risk management information systems (d) a comprehensive internal control system. The benefits for the bank are the progress and health of the bank and the benefits for customers, namely the ease of owning a house and applying for Griya Hasanah product financing.